Overweight and decreased baroreflex sensitivity as independent risk factors for hypertension in children, adolescents, and young adults - Krontorádová, K; Honzíková, N; Fiser, B; Nováková, Z; Závodná, E; Hrstková, H; Honzík, P (Physiological research, 2008)
We studied the relationship between blood pressure (BP), body mass index (BMI, kg/m(2)) and baroreflex sensitivity (BRS, ms/mmHg) in adolescents. We examined 34 subjects aged 16.2+/-2.4 years who had repeatedly high causal BP (H) and 52 controls (C) aged 16.4+/-2.2 years. Forty-four C and 22 H were of normal weight (BMI between 19-23.9), and 8 C and 12 H were overweight (BMI between 24-30). Systolic BP was recorded beat-to-beat for 5 min (Finapres, controlled breathing 0.33 Hz). BRS was determined by the cross-spectral method. The predicting power of BMI and BRS for hypertension was evaluated by sensitivity, specificity, and receiver operating curve (ROC - plot of sensitivity versus specificity). H compared with C had lower BRS (p<0.01) and higher BMI (p<0.05). Multiple logistic regression analysis (p<0.001) revealed that a decreased BRS (p<0.05) and an increased BMI (p<0.01) were independently associated with an increased risk of hypertension. No correlation between BMI and BRS was found either in H or in C. Following optimal critical values by ROC, the sensitivity, specificity and area under ROC were determined for: BMI - 22.2 kg/m(2), 61.8 %, 69.2 %, 66.0 %; BRS - 7.1 ms/mmHg, 67.7 %, 69.2 %, 70.0 %; BMI and BRS - 0.439 a.u., 73.5 %, 82.7 %, and 77.3 %. Decreased BRS and overweight were found to be independent risk factors for hypertension.
Keywords: dospělí; studie případů a kontrol; index tělesné hmotnosti; Predictive Value of Tests; Humans; Risk Assessment; logistické modely; Hypertension; Logistic Models; Sensitivity and Specificity; Blood Pressure; Body Mass Index; Risk Factors; mužské pohlaví; Age Factors; Overweight; ROC Curve; Adult; krevní tlak; baroreflex; Adolescent; rizikové faktory; ženské pohlaví; věkové faktory; ROC křivka; nadváha; hypertenze; hodnocení rizik; lidé; senzitivita a specificita; mladiství; Case-Control Studies; dítě; Child; Baroreflex; Systole; prediktivní hodnota testů; Male; systola; Female